(untitled) (LEARNing Landscapes, 2019)
This paper explores the pedagogical implications of using arts-based research in an advanced community practice course in a Master of Social Work program. Per the course design, graduate students implemented a photovoice project with undergraduate students focusing on transforming campus rape culture. At the end of the project, graduate students wrote reflection papers that constitute the data for this paper. The data analysis resulted in three categories: enhancing the learning of content, understanding the role of a social worker in macro-level practice, and engaging with the community.